Congestion Pricing in Urban Polycentric Networks with Distorted Labor Markets: A Spatial General Equilibrium Model for the Area Randstad - Ioannis Tikoudis (Tinbergen Institute, 2015)
The paper presents a polycentric general equilibrium model with congestion externalities and distortionary labor taxation calibrated to fit the key empirical regularities of the regional economy and transport system of Randstad conglomeration. In line with more stylized models, marginal external cost pricing (i.e. a quasi first-best Pigouvian toll that ignores the pre-existing taxation in the labor market) is shown to generate considerable welfare losses. Surprisingly, the quasi first-best Pigouvian toll is welfare decreasing even when the road tax revenue is used to finance labor tax cuts. This is due to the large deviation of marginal external costs from the optimal toll levels, as the latter are found to be negative in many of the network links. Approximations of the key double-dividend effects show that, in those links, the tax interaction effect is strong enough to outweigh both the revenue-recycling and the Pigouvian effect.
Keywords: D58; H21; H23; C63; R13; R40; 330; applied general equilibrium; network; road pricing; commuting; polycentricity; environmental taxation; double-dividend